2014
DOI: 10.1016/j.fuel.2014.07.099
|View full text |Cite
|
Sign up to set email alerts
|

Two-step process for production of biodiesel blends from oleaginous yeast and microalgae

Abstract: Biodiesel produced from oleaginous microorganisms shows promise in displacing use of petroleum diesel fuel, however, low biodiesel yields and rigorous processing have thwarted largescale commercialization. Here, we report a simple and efficient two-step process for generating biodiesel blends from microbial biomass, which eliminates the need for solvent extractions, distillations, or additional purifications. In the present work, diesel fuel was utilized to extract biodiesel produced from direct transesterific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Previous reports used pure sucrose, synthetic media, pre‐treated secondary wastewater sludge, and pre‐treated microalgae hydrolysate fed with pure glucose as cultivation media for oily yeasts. Conversely, T. oleaginosus was successfully cultivated in all hydrolysates of aged‐seagrass as the sole carbon source, without expensive additives such as yeast extract and biotin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports used pure sucrose, synthetic media, pre‐treated secondary wastewater sludge, and pre‐treated microalgae hydrolysate fed with pure glucose as cultivation media for oily yeasts. Conversely, T. oleaginosus was successfully cultivated in all hydrolysates of aged‐seagrass as the sole carbon source, without expensive additives such as yeast extract and biotin.…”
Section: Resultsmentioning
confidence: 99%
“…McCurdy et al., showed that lipids from T. oleaginosus can be converted into biodiesel with a recovery of 98.9 %. Furthermore, flash point, viscosity, sulfur content, and acid number of the corresponding B20 meet the ASTM requirement and it is comparable to Soybean B20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all of them were within the limit of ASTM/ BIS standards (Table 7) (McCurdy et al 2014;Diesel Net Technology Guide 2009). The kinematic viscosity of the biodiesel was just a little higher than the petroleum diesel (3 mm 2 /s).…”
Section: Biodiesel Characteristicsmentioning
confidence: 75%
“…Studies on renewable liquid fuel production demonstrate that large-scale production can replace petroleum derived fuels (Brown and Brown, 2013;Mccurdy et al, 2014). Biodiesel is one of the most promising renewable fuel, and has been produced from various raw feedstocks such as oil from crops and residual oils (Vasudevan and Briggs, 2008).…”
Section: Introductionmentioning
confidence: 99%